The use of mechanical ventilation and air-conditioning in buildings (known as the SAA Mechanical Ventilation and Air-conditioning Code) Part 1. Fire precautions in buildings with air-handling systems - Standards Australia (Sydney, NSW SA, 1979)
Applies to the design, construction, installation and operation of air-handling systems in relation to fire protection of buildings. It is intended to assist in the prevention of fire and the spreading of the products of combustion through a building by the air-handling system.
Superseded By : AS 1668.1-1991
Supersedes: DR 76053
Keywords: Ventilation and air-conditioning -- Standards